Writing under the gaze: Plagiarism policies and international ESL students patchwriting in graduate school - Abasi, Ali Reza (University of Ottawa (Canada), 2008)
In this study I investigated how seven English-as-a-Second-Language (ESL) international students at two graduate programs at the University of Ottawa wrote course papers in light of the university's policies on plagiarism. Informed by the New Literacy Studies, Bourdieu's social theory, Bakhtin's theory of language, and Ivanic's analytical framework of writer identity, the inquiry drew upon multiple sources of data involving field observations, artifact analysis, and interviews with the students, their course professors, and other faculty members over two consecutive academic sessions. The results indicate that patchwriting, defined as one writer working closely with other writers' texts while leaving behind traces of those texts (Howard, 1999), is a major strategy through which students make other peoples' words and ideas their own. The study further differentiates between localized patchwriting and global patchwriting, and offers an account of the reasons that give rise to each. It also discusses how educational practice simultaneously calls upon students to write as professionals and students, and considers the role that university plagiarism policies play in students' decision as to which identity to take up and textually enact. The study discusses faculty's mediation of plagiarism policies, and identifies a dissonance between their pedagogic response and the university's legalistic treatment of student textual borrowing practices that violate common practice. The research also considers the impact of institutional plagiarism policies on students and professors, and makes suggestions for the re-consideration of university plagiarism policies and documents.
Keywords: Education, Bilingual and Multicultural.; Language, Rhetoric and Composition.; Education, Higher.